IMPACT OF GOVERNAMENTAL POLICIES IN LEGISLATION AFTER THE GLOBAL FINANCIAL CRISIS – ESPECIALLY IN KOSOVO - Krasniqi, Armand (Journal of Advanced Studies in Finance, 2010)
Treating the negative effects caused by the global financial crisis is a task of state institutions. Concerned for the impact of these effects, governments are carrying out and implementing state policies through implementing political, legal and economical measures against the logic of economical liberalization. This government activity in the function of regulating economic relations is being performed through carrying out and implementing non-tariff economical barriers even though such actions are against the principles of the most important international institutions and the logic of liberal development itself. Due to the significance this crisis has and is going to have even with the emergence of forms of criminality, state institutions should rapidly get back to finding efficient monetary, financial and legal measures and policies for rescue. The role of state intervention not only is inevitable, but it is necessary and the actions should be realistic, rational, efficient, and constructive. The first result emerging from this situation is the fact that now banks and other institutions are creating special bounds with the state. The role of state should focus through integrated political, economical and legislative strategies towards strengthening the bank system, credit market system, protection of investments, change of tax policies, capital stimulation, and fighting crime. All this should reflect an anti-crisis strategy which at the very least would immunize the economical systems in countries attacked by the crisis.